2014
DOI: 10.1063/1.4885770
|View full text |Cite
|
Sign up to set email alerts
|

Voltage polarity manipulation of the magnetoresistance sign in organic spin valve devices

Abstract: The spin transport in organic spin valve (OSV) devices has been systematically investigated by inserting a low work function material Al between ferromagnetic electrode and organic layer. The resistance and current-voltage curve symmetry are dramatically altered as increasing Al thickness, indicating that an electron-unipolar OSV is obtained. Moreover, the magnetoresistance sign depends on the voltage polarity for certain Al thickness. We attribute this phenomenon to the Fermi and the lowest unoccupied molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Subsequently, in a similar device, they realized a universal logic gate for information processing by modulating the programing voltage and magnetic field configuration . Furthermore, electrically controlled MR with tunable magnitude and sign is obtained by Jiang et al and Göckeritz et al, respectively, which further demonstrates the possibility as multistate memory. Particularly, the typical device configuration of LSMO/Alq 3 /Co, employed in these studies, can lead to diverse device functions according to many previous reports .…”
Section: Interactive‐type Functional Molecular Spintronic Devicesmentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequently, in a similar device, they realized a universal logic gate for information processing by modulating the programing voltage and magnetic field configuration . Furthermore, electrically controlled MR with tunable magnitude and sign is obtained by Jiang et al and Göckeritz et al, respectively, which further demonstrates the possibility as multistate memory. Particularly, the typical device configuration of LSMO/Alq 3 /Co, employed in these studies, can lead to diverse device functions according to many previous reports .…”
Section: Interactive‐type Functional Molecular Spintronic Devicesmentioning
confidence: 98%
“…According to the studies regarding multifunctional memories as mentioned, above all, the device performance, especially when at RT, still needs to be greatly improved before discussing its application. Moreover, the mechanism of multifunction in those devices still needs to be further clarified since multiple mechanisms including charge trapping, filament conduction, energy level change, pinhole transport, and interfacial dipole modification have been suggested by previous studies.…”
Section: Interactive‐type Functional Molecular Spintronic Devicesmentioning
confidence: 99%
“…It has been shown that the manipulation of energy band alignment between a ferromagnetic metal and an organic semiconductor can be achieved simply by introducing a thin interlayer of an appropriate work function material, such as a 1 nm thick LiF at their interface . Adjustment of energy band alignment by inserting an interlayer may enable selective charge carrier (electrons or holes) or selective spin polarity (majority or minority spins) at the carrier injection/extraction electrode. For the Alq 3 , the transport of an electron as a spin carrier can be preferable to that of a hole because the electron mobility is one to two orders of magnitude higher than that of holes .…”
Section: Tuning Of Band Alignment At the Interface By A Low Work Funcmentioning
confidence: 99%
“…The main cause for device degradation is likely different in Co/Alq 3 /NiFe and Co/Ca/Alq 3 /Ca/NiFe; the former can be attributed to the excessive hole injection resulting in the formation of unstable cationic Alq 3 species while the latter is possibly due to the break‐down of Alq 3 by Ca layers . Recent findings suggest that a thin Al interlayer may also facilitate spin‐polarized electron injection/extraction in the Alq 3 spin‐valve devices with ferromagnetic electrodes …”
Section: Tuning Of Band Alignment At the Interface By A Low Work Funcmentioning
confidence: 99%
“…Here we review the FE control of MR in organic spin valves as one of the frontiers of organic spintronics. Inspired by similar work in inorganic spin valves and previous efforts in tuning FM/organic interfaces [23][24][25][26][27][28][29][30][31], recently, a sequence of work has studied the multistates in the organic spin valves using FE materials as the spacer or as an interfacial layer. [32][33][34][35] The results confirm the critical role of energy alignment and interfacial structure in the spinterface.…”
Section: Introductionmentioning
confidence: 99%